An overview of the Rio Algom expansion program at Elliot Lake, Ontario - K. B. Culver (Canadian Institute of Mining, Metallurgy and Petroleum, 1980)
"This paper provides background information on the expansion programs of Rio Algom Limited at Elliot Lake. Included are details on the Quirke expansion program, the Panel mine rehabilitation program, including the selection procedure for the tailings containment area, the Stanleigh mine rehabilitation program, housing, government regulations and the Environmental Assessment Board hearings. Introduction After 2Y2 years of public hearings, 4 years of arbritrating differences of opinion between our engineers and government licencing authorities, interspersed with research into radium removal and development of the LAMIX process and carrying out the work associated with some 24 control orders issued to us by the MOE, it is very difficult to compress all of the experiences and frustrations into a single paper. The highlights, as they relate to the expansion programs of Rio Algorn Limited and its affiliate, Preston Mines Limited, will be covered. Denison Mines Limited, of course, is the other uranium producer in Elliot Lake. They are currently in the process of expanding from 7,000 to 11,000 TPD by the second half of 1980 and then to 15,000 TPD by the mid 1980's. In giving this overview, the following seven items will be discussed: • The basis for Rio Algom's and Preston's expansion plans. • The Quirke Expansion. • The Panel Rehabilitation. • The Stanleigh Rehabilitation. • Housing Programs. • Government Licencing Requirements. • Environmental Assessment Board Hearings."